2013
DOI: 10.1007/s12264-013-1342-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of carbenoxolone are associated with attenuation of oxidative stress in ischemic brain injury

Abstract: Accumulating evidence has suggested that the gap junction plays an important role in the determination of cerebral ischemia, but the underlying mechanisms remain to be elucidated. In this study, we assessed the effect of a gap-junction blocker, carbenoxolone (CBX), on ischemia/reperfusion-induced brain injury and the possible mechanisms. By using the transient cerebral ischemia model induced by occlusion of the middle cerebral artery for 30 min followed by reperfusion for 24 h, we found that pre-administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The Cx family is characterized by 20 isoforms expressed in the mouse genome; however, it has been determined that approximately half of the Cx isoforms are present in the brain. Interestingly, following previous reports, it has been observed that GJ blockers mainly modify the communication of GJ and hemichannels constituted of Cx36, Cx43 and Cx50 (Table 1 ) [ 36 , 37 , 61 , 75 , 89 , 90 , 99 - 105 ]. Of all the Cx isoforms expressed in the brain, it has been proposed that Cx36 is the major neuronal isoform and consequently plays an essential role in the generation of highly synchronized electrical activity.…”
Section: Gj or Hemichannels As Targets Of Gj Blockerssupporting
confidence: 68%
See 1 more Smart Citation
“…The Cx family is characterized by 20 isoforms expressed in the mouse genome; however, it has been determined that approximately half of the Cx isoforms are present in the brain. Interestingly, following previous reports, it has been observed that GJ blockers mainly modify the communication of GJ and hemichannels constituted of Cx36, Cx43 and Cx50 (Table 1 ) [ 36 , 37 , 61 , 75 , 89 , 90 , 99 - 105 ]. Of all the Cx isoforms expressed in the brain, it has been proposed that Cx36 is the major neuronal isoform and consequently plays an essential role in the generation of highly synchronized electrical activity.…”
Section: Gj or Hemichannels As Targets Of Gj Blockerssupporting
confidence: 68%
“…Interestingly, it was demonstrated that CBX produced inhibition of the gap junctional intercellular communication but without a clear selectivity for particular subtypes of Cx [ 34 , 35 ]. After this discovery, many studies focused on evaluating CBX in diverse models of processes related to the gap junctional intercellular communication in the brain [ 36 , 37 ].…”
Section: Gj Blockers and Animal Seizure Modelsmentioning
confidence: 99%
“…Based on studies in the heart and brain, it was proposed that metabolic inhibition from an ischemic episode opens CxHCs upon reperfusion, which accelerates cell death ( Clarke et al, 2009 ; Contreras et al, 2002 ; Davidson et al, 2013 ; Johansen et al, 2011 ; Orellana et al, 2010 ; Thompson et al, 2006 ). In addition, increases in Cx43 expression and GJIC were suggested to play a role in the spread of damage through the ‘bystander’ effect when cell death signals spread laterally through GJ from dying cells to their healthy neighbours ( Cotrina et al, 1998 ; Danesh-Meyer et al, 2012 ; Davidson et al, 2012 ; Mao et al, 2009 ; Zhang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The spread of cell death has been attributed to GJIC in stroke models ( Cotrina et al, 1998 ) and models of heart attack ( García-Dorado et al, 2004 ) whilst negative effects of CxHC activity on cell viability have been reported in models of stroke ( Cotrina et al, 1998 ; García-Dorado et al, 2004 ; Orellana et al, 2010 ; Thompson et al, 2006 ). The ‘bystander’ effect model suggests that death signals can spread laterally through GJs from dying cells into their healthy neighbour cells ( Mao et al, 2009 ; Zhang et al, 2013 ). However, some reports also attribute cell death in ischemia-reperfusion models to the opening of undocked CxHC, causing blood vessel leakiness and release of ATP leading to activation of purinergic receptors ( Danesh-Meyer et al, 2012 ; Clarke et al, 2009 ; Davidson et al, 2013 ; Orellana et al, 2010 ; Poornima et al, 2012 ; Thompson et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, Gap27 was found to increase phosphorylation of S368 without altering the level of Cx43 (Evans and Boitano, 2001). It was suggested that Gap27 prevents the death of a number of cell types, including cardiomyocytes, cortical astrocytes and neurons, by blocking Cx43 opening during reperfusion (Thompson et al, 2006; Clarke et al, 2009; Orellana et al, 2010), as well as preventing “bystander effect” of cell death induction of healthy cells in close proximity (Mao et al, 2009; Danesh-Meyer et al, 2012; Zhang et al, 2013). Further investigations into the potential of Gap27 and other connexin modulators for clinical use will be the next step in improving treatment options for pressure ulcers.…”
Section: Pressure Ulcersmentioning
confidence: 99%